Les données fondamentales du dvenir de la politique étrangère canadienne : Essai de synthèse - Soldatos, Panayotis (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
This paper proposes to grasp the main issues of Canadian foreign policy in the eighties by using an analysis framework based on the concepts of fragmentation, continentalism and diversification, considered as the intervening variables in the process of explaining Canada's international behaviour. Emphasizing the explanatory variables of the three phenomena (fragmentation, continentalism, diversification), the study demonstrates their complexity, namely the multiplicity of their causes, and underlines some of their basic characteristics, such as the structural sources of Canadian fragmentation in foreign policy - closely relate d to the nature of the country's economy and its links with the United States -, the ambiguity and shortcomings of the continentalist option, and the contradictions of the diversification policies. Beyond that, the paper attempts to indicate the interrelation of the three phenomena, their constant and circular interaction, and their future directions. Finally, the text deals with the question of a general theoretical framework for the study of these main issues in Canadian foreign policy.